Sustainable development goals knowledge and sustainability behaviour: a study of British and Malaysian tertiary students / Ronghui Zhou, Nur Fadhlina Zainal Abedin and Sheela Paramasivam - Ronghui, Zhou; Zainal Abedin, Nur Fadhlina; Paramasivam, Sheela (Universiti Teknologi MARA, 2022)
This paper explores Sustainable Development Goals (SDGs) knowledge and behavioural differences of university students in the United Kingdom and Malaysia. The researchers also explore gender as an indicator of students’ SDG awareness and behaviours as few studies to date have explored this area. This study employed a sustainability consciousness questionnaire (SCQ) that was developed to measure SDG knowledge based on the UNESCO framework for sustainability behaviour. Questionnaires were distributed to 156 university students in the UK and Malaysia. Malaysian university students reported higher scores for understanding SDG content and scope and the specific SDGs of their country compared to British students, although British students have been receiving formal education on SDGs. University students in the UK were also unable to transform their SDG knowledge into sustainability behaviours, although they had a certain level of understanding of the topic covered by the SDGs. Malaysian university students exhibited a closer relationship between SDG knowledge and sustainable behaviours given the sufficient institutional and policy support and customised university programs. SDG knowledge and sustainability behaviours were the same for male and female students in both countries. In conclusion, integrating SDG knowledge into university education will inevitably lead students to work towards SDG goals in the future. This can be achieved with proper planning of the university curriculum and the enforcement of educational policies.